2022
DOI: 10.1080/14786419.2022.2162896
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of anti-inflammatory and analgesic polysaccharides from Coix seed ( Coix lacryma-jobi L.var. Ma-yuen (Roman.) Stapf )

Abstract: Coix seed is a nutrient-rich food and traditional Chinese medicine with anti-inflammatory and analgesic properties. Polysaccharides from Coix seed have been rarely investigated for structure and activities. In this study, the analgesic and anti-inflammatory effects were investigated in vivo and in vitro. The results showed that Coix seed had a significant influence on reducing the number of writhing, increasing the pain threshold and alleviating the swelling degree caused by acute inflammation. Column chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In this experiment, the CHD model of rats was established by intraperitoneal injection of adriamycin, and the rats were treated with captopril and different doses of YYFZ, and the efficacy of YYFZ was comprehensively evaluated by observing the biochemical indexes and cardiac function indexes of rats and myocardial histopathological sections. Adriamycin belongs to anthracycline antibiotics, which are widely used in clinical practice for the treatment of various malignant tumors (Sabatino et al, 2020;Younis et al, 2021;Xu et al, 2022). Cardiotoxicity is one of its main side effects, which can be manifested as irreversible dosedependent cardiomyopathy and CHD, so a heart failure model was prepared using this side effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, the CHD model of rats was established by intraperitoneal injection of adriamycin, and the rats were treated with captopril and different doses of YYFZ, and the efficacy of YYFZ was comprehensively evaluated by observing the biochemical indexes and cardiac function indexes of rats and myocardial histopathological sections. Adriamycin belongs to anthracycline antibiotics, which are widely used in clinical practice for the treatment of various malignant tumors (Sabatino et al, 2020;Younis et al, 2021;Xu et al, 2022). Cardiotoxicity is one of its main side effects, which can be manifested as irreversible dosedependent cardiomyopathy and CHD, so a heart failure model was prepared using this side effect.…”
Section: Discussionmentioning
confidence: 99%
“…This formula is from the book "Jin Gui Yao Lve." Coix seed has multiple pharmacological effects such as anti-tumor, improving body immunity, hypoglycemia, anti-inflammatory and analgesic, and regulating lipid metabolism, and its important pharmacological activities in the treatment of cervical cancer, lung cancer, and gastrointestinal tract tumors have been confirmed in clinical practice (Ni et al, 2021;Zhou et al, 2021;Sui and Xu, 2022;. In a related experimental study, Coix seed was found to improve Th1/ Th2 cytokines in mice to restore immune homeostasis after administration (Wang H. et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This powder is commonly used in China to treat various inflammatory conditions such as arthritis and myocarditis (Liu, 1991;Zhang F. F. et al, 2023;Wang Y. Y. et al, 2023). Its anti-inflammatory effects are attributed to its active components, including flavonoids, stilbenes, and anthraquinones (Chung et al, 2010;Zhu, 2017;Feng et al, 2021;Sui and Xu, 2022).…”
Section: Inhibiting Inflammatory Responsesmentioning
confidence: 99%
“…and Mashinin (Cannabis Fructus). Some studies have analyzed lowmolecular compounds or polysaccharides that can be extracted into a low-polarity solvent in Yokuinin and investigated their effects in vitro and in vivo [63][64][65][66][67][68][69]. However, Li et al extracted the components in Yokuinin using high-polarity solvents, namely, 0.5 M sodium chloride aqueous, 70% ethanol aqueous, and 12.5 mM sodium borate buffer [18]; these four solvents contained albumin, globulin, prolamin, and glutelin, and their target was glutelin.…”
Section: Proteins In Crude Drugsmentioning
confidence: 99%